Evaluation of Pedestrian Way’s Comfort Case Study: Jl. Z. A. Pagar Alam, Bandar Lampung - Haris Murwadi; Fritz Akhmad Nuzir (Bandar Lampung University (UBL), 2014)
The phenomenon of many pedestrians, especially students who use the road into the background of this research. Allegations that the walkers feel comfortable with walking on the body road and many similar case that found. This study was aimed to evaluate and determine the factors that influence the comfort of the pedestrian way users on Jalan Zainal Abidin Pagar Alam (hereinafter referred as the ZAPA Street) as well as to know the expectations of the convenience factors from the respondents. This study used qualitative methods which were content analysis and comparative analysis.This study found that discomfort occurs due to physical, non-physical, and obstacle factors. Discomfort on physical factors such as the design aspect (width, continuous, flatness, modernity, aesthetic, and not slippery) and treatment aspect (damaged, holes, and drainage holes). Discomfort on non-physical factors such as safety aspect (hazards, advertisements, roof spans, and curves) and aspect sensory responses aspect (heat/rain, smell, vegetation, and dirty). While discomfort on the obstacles such as permanent aspect and non-permanent aspect. The dominant physical discomforts were shown by the damages, holes which were found in the walkway, height of elevation, surface flatness, slope, and un-finished parts. Meanwhile the dominant non-physical discomforts were shown by the dirtiness of the walkway and the span of billboards and roof structures.